2009
DOI: 10.1021/bc9000933
|View full text |Cite
|
Sign up to set email alerts
|

Optical Antisense Tumor Targeting in Vivo with an Improved Fluorescent DNA Duplex Probe

Abstract: Fluorescent conjugated DNA oligonucleotides for antisense targeting of mRNA has the potential of improving tumor/normal tissue ratios over that achievable by nuclear antisense imaging. By conjugating the Cy5.5 emitter to the 3′ equivalent end of a 25 mer phosphorothioate (PS) antisense major DNA and hybridizing with a shorter 18 mer phosphodiester (PO) complementary minor DNA (cDNA) with the Black Hole inhibitor BHQ3 on its 5′ end (i.e., PS DNA25-Cy5.5/PO cDNA18-BHQ3), we previously achieved antisense optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Thiazole Orange is a commercially available, high quantum yield fluorophore that emits strong fluorescence upon binding to nucleic acids, resulting in highly sensitive nucleic acid sensing and DNA imaging . This fluorophore has been conjugated to peptides, DNA, RNA, and other oligonucleotide variants, and its high cell permeability and intracellular stability means that these tagged macromolecules can be readily imaged in vivo. , Because the fluorescence of Thiazole Orange is highly sensitive to the presence of exogenous contaminants, it can be used for the detection of a broad variety of analytes, including tetracycline, an antibiotic; cations; , melamine, a highly toxic compound used in the production of plastics; and other analytes of interest. , …”
Section: Common Fluorophoresmentioning
confidence: 99%
“…Thiazole Orange is a commercially available, high quantum yield fluorophore that emits strong fluorescence upon binding to nucleic acids, resulting in highly sensitive nucleic acid sensing and DNA imaging . This fluorophore has been conjugated to peptides, DNA, RNA, and other oligonucleotide variants, and its high cell permeability and intracellular stability means that these tagged macromolecules can be readily imaged in vivo. , Because the fluorescence of Thiazole Orange is highly sensitive to the presence of exogenous contaminants, it can be used for the detection of a broad variety of analytes, including tetracycline, an antibiotic; cations; , melamine, a highly toxic compound used in the production of plastics; and other analytes of interest. , …”
Section: Common Fluorophoresmentioning
confidence: 99%
“…Based on the experience of this laboratory with numerous oligomer backbone chemistries [9,19,20,29], and the work of others [30,31], the three oligomer backbone chemistries selected for these studies were PS-DNA, PNA and MORF.…”
Section: Discussionmentioning
confidence: 99%
“…Since the phosphodiester DNA is unstable to nucleases [17], and since the pharmacokinetics and binding properties of oligomers can depend on their structure [18] three different oligomer types were studied as alternatives to the native phosphodiester DNA: PNA; phosphorothioate DNA (PS-DNA) and MORF. Each oligomer type has previously been radiolabeled in this laboratory with 99m Tc for various applications [9,10,19,20]. These oligomers differ in the linkages between the bases and in charge, but each is stable to nucleases and each maintains the proper structure for complementary base pairing and stable hybridization.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that this probe could image a complementary biotinylated 25-mer MORF oligomer immobilized on streptavidin polystyrene microspheres that were intramuscularly implanted into a mouse [ 14 ]. The same group also utilized a probe consisting of a 25-mer phosphorothioate DNA bearing Cy5.5 and a 10-mer complementary ODN with the BHQ3 quencher to image the KB-G2 tumor in mice which overexpresses the multi-drug-resistant mdr1 mRNA [ 15 ]. In another approach, Mirkin and coworkers developed “nanoflares” in which antisense ODNs to a target mRNA are conjugated to a gold nanoparticle and then hybridized to a shorter strand of complementary DNA bearing Cy5 which is quenched by the gold nanoparticle.…”
Section: Introductionmentioning
confidence: 99%